2022
DOI: 10.1093/g3journal/jkac297
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics analysis of the mechanisms behind flavonoid differences between purple and green tender shoots of Camellia sinensis var. assamica

Abstract: Flavonoids are rich in tea plants (Camellia sinensis), and responsible for the flavor and healthful benefits of tea beverage. The anthocyanin levels in the purple tender shoots are higher than in the general green leaves of tea plant, which provide special materials to search metabolic mechanisms of flavonoid enrichment in plant. In this work, flavonoid differences between purple and green shoots from tea cultivars ‘Zijuan’ (ZJ) and ‘Yunkang10’ (YK-10) were investigated through metabolomic analysis, and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In the present study, flavonoids accounted for the majority of the total differential metabolites between MK and FY. This is similar to the previous findings in that cultivar is an important factor affecting the differences in flavonoid content [44,45]. Furthermore, we found that most of the anthocyanin-like differential metabolites detected had higher accumulation in MK.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, flavonoids accounted for the majority of the total differential metabolites between MK and FY. This is similar to the previous findings in that cultivar is an important factor affecting the differences in flavonoid content [44,45]. Furthermore, we found that most of the anthocyanin-like differential metabolites detected had higher accumulation in MK.…”
Section: Discussionsupporting
confidence: 92%
“…Performing the overexpression of MYB90 from Zikui in the calluses of tobacco can strongly induce anthocyanin syn- Besides the genetic factors, environmental variations also influence the anthocyanin composition [93]. For instance, in the most studied purple variety, Zijuan, delphinidin-3-O-galactoside is detected at high levels in five different geographical environments but not in 'Pu'er' [77,82,[87][88][89]91]. The components of anthocyanin identified also depend on the detection strategy.…”
Section: Molecular Mechanisms Of Purple Coloration In Tea Leavesmentioning
confidence: 99%
“…On the other hand, CsUGT94P1 preferentially xylosylated the sugar moiety of geranyl glucoside at the 6’-hydroxy group, but was also able to use UDP-glucose as a donor substrate, albeit with one-third reduction in activity, and can therefore also be classed as a GGT. CsUGT94P1 gene expression correlated with flavonoid content in shoots of two metabolically distinct tea cultivars ( Liu et al., 2023 ).…”
Section: Functionally Characterized Ugts From the Tea Plantmentioning
confidence: 99%
“…In both transgenic plant species, CsUGT78A14 promoted flavonol 3- O -glucoside production, whereas flavonol 3- O -galactosides accumulated in CsUGT78A15 transgenic plants. In a multiomics analysis, CsUGT78A15 protein content correlated with flavonoid content in the shoots of two metabolically distinct tea genotypes ( Liu et al., 2023 ).…”
Section: Functionally Characterized Ugts From the Tea Plantmentioning
confidence: 99%
See 1 more Smart Citation